Development and strategies of VEGFR-2/KDR inhibitors. (September 2012) - Huang, Lingyi; Huang, Zhengui; Bai, Zhiqiang; Xie, Rui; Sun, Liping; Lin, Kejiang
VEGF is an important signaling protein involved in both vasculogenesis and angiogenesis. As an essential receptor protein tyrosine kinase propagating cellular signal transduction processes, VEGFR-2 is a central target for drug discovery against tumor-associated angiogenesis. Since the autophosphorylation of VEGFR-2 represents a key step in this signal pathway that contributes to angiogenesis, the discovery of small molecule inhibitors that block this reaction has attracted great interest for novel drugs research and development. Advances in the understanding of catalytic cleft and the conformational changes of DFG motif have resulted in the development of small molecule inhibitors known as type I and type II. High-resolution crystal structures of various inhibitors in complex with the receptor offer an insight into the relationship among binding modes, inhibition mechanisms, activity, selectivity and resistance. To control selectivity, improve activity and introduce intellectual property novelty, the strategies for the further development are discussed through structural and conformational analysis in this review.